2019
DOI: 10.31883/pjfns/112654
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity of Extracts of Soursop (Annona muricata L.) Leaves, Fruit Pulps, Peels, and Seeds

Abstract: Aromatic soursop fruits are readily used culinary. Pulp is consumed raw and is used to prepare juice, ice-cream or jelly [Benites et al., 2015]. Moreover, different parts of soursop (leaf, bark, root, fruit, and seed) are used in traditional medicine against several ailments including hypertension, infl ammation, diabetes, gastrointestinal disorders, respiratory diseases, and cancers [Coria-Tellez et al., 2018; Chamcheu et al., 2018]. The medicinal activities and the health benefi ts of A. muricata L. have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 34 publications
2
23
2
1
Order By: Relevance
“…In the literature, SOX extraction yield of GP is approximately 60,00 % [5], a value close to that obtained by this study (64,65 %). However, in the case of SP, values from 0,23 to 16,50 % are reported [20], showing a significant difference with the ones found in this work (50,63 %). This is possibly due to the use of other solvents, for example, methanol, hexane, or ethyl acetate, as well as the extraction temperature (room temperature) [20].…”
Section: Soxhlet Extractioncontrasting
confidence: 94%
“…In the literature, SOX extraction yield of GP is approximately 60,00 % [5], a value close to that obtained by this study (64,65 %). However, in the case of SP, values from 0,23 to 16,50 % are reported [20], showing a significant difference with the ones found in this work (50,63 %). This is possibly due to the use of other solvents, for example, methanol, hexane, or ethyl acetate, as well as the extraction temperature (room temperature) [20].…”
Section: Soxhlet Extractioncontrasting
confidence: 94%
“…Besides, the seed extracts exhibited the highest CUPRAC, FRAP, TEAC, and DPPH scavenging activity, followed by leaf and peel extracts. Additionally, methanol seed extracts possessed the highest total phenolic content compared to all the other solvents extracts used in the study ( Orak et al, 2019 ). Similarly, in the present study, the IR spectrum of seed extract showed two additional peaks (1320 cm −1 and 1738 cm −1 ) which were not found in the IR spectrum of pulp extract.…”
Section: Resultsmentioning
confidence: 98%
“…The cupric ion reducing antioxidant capacity was determined according to a method described previously [ 18 ], with some modifications. Extract solution (0.5 mL) was added into a reaction mixture containing CuCl 2 (10 mM, 1 mL), neocuproine in ethanol (7.5 mM, 1 mL), and NH 4 OAc buffer (1 M, 1 mL, pH 7.00).…”
Section: Methodsmentioning
confidence: 99%